KOMUNIKASI HEALTH EDUCATION TERHADAP PENGETAHUAN LANSIA TENTANG PERTOLONGAN PERTAMA PADA DIAREDI WILAYAH KERJA PUSKESMAS NGADILUWIH KABUPATEN KEDIRI - Prima Dewi Kusumawati; Nafa Zunaidah Fahma; Dhita Kurnia Sari (Universitas Merdeka Malang, 2017)
Abstract The delay of the first aid on the elderly’s diarrhea to prevent complications like dehydration was caused due to the lack of knowledge about its first aid. Communication of health education is a way to increase their knowledge. The purpose of this research is to know the influence of health education to the elderly’s knowledge about first aid on diarrhea in working area of Ngadiluwih Health Center Kediri Regency. Research design used in this research was pre-experimental with one-group pra-post test. Population was all ≥60 years old elderly who were active in elderly’s health center and lived in Tales Village Working Area Health Center Ngadiluwih Kediri with 98 samples taken by simple random sampling. The instrument used pre-post test knowledge questionnaires about first aid on diarrhea and then analyzed by Wilcoxon Test. The results of elderly before having health education about first aid on diarrhea, there were 83 respondents (84.6%) who were less knowledgeable, while after having health education 85 respondents (86.7%) were either knowledgeable. Wilcoxon test with p value = 0.000 0.05 thenrefore H0 is rejected, which means there was influence of health education on elderly’s knowledge about first aid on diarrhea in working area of Ngadiluwih Health Center Kediri Regency. Health education and direct information can increase knowledge. Keywords: Communication of health education, knowledge, First aid on diarrhea, Elderly DOI : https://doi.org/10.26905/nomosleca.v3i2.2035